Length of Stay, Mortality, Cost, and Perceptions of Care Associated With Transition From an Open to Closed Staffing Model in the Cardiac Intensive Care Unit. Issue 2 (June 2017) - Katz, Jason N.; Lishmanov, Anton; van Diepen, Sean; Yu, Dongqing; Shen, Haipeng; Pauley, Eric; Bhatia, Jatin; Buntaine, Adam; Das, Arun; Dangerfield, Cristie; McLaughlin, Brooke; Stouffer, George A.; et al.
Abstract : Background: Organizational models in the intensive care unit (ICU) have classically been described as either closed or open, depending on the presence or absence of a dedicated ICU team. Although a closed model has been shown to improve patient outcomes in medical and surgical ICUs, the merits of various care models have not been previously explored in the cardiac ICU (CICU) setting. Methods: From November 2012 to March 2014, data were prospectively collected on all admissions before and after transition from an open to closed CICU at our institution. Baseline clinical variables, illness severity, admission and discharge diagnoses, resource use, and outcomes were recorded. Anonymous surveys were also collected from nursing and resident trainee participants to evaluate the influence of unit structure on perceptions of care. Descriptive statistics were used, and logistic regression modeling was performed to examine the impact of unit structure on mortality. Results: The study consisted of 670 patients, 332 (49.6%) of whom were admitted to the open CICU model and 338 (50.4%) of whom were admitted to the closed model. Neither CICU nor hospital mortality differed between the open and closed units, though length of stay was shorter in the closed CICU. Additionally, nurses and resident trainees reported that the closed CICU allowed for better communication, collaboration, and education. Conclusions: Although there was no significant impact of unit structure on patient outcomes in this single-center study, the closed CICU model was associated with better perceptions of care.